Analisis Faktor Kesuksesan E-Learning dalam Meningkatkan Kualitas Belajar Mengajar di Kota Batam - Firmansyah, Muhamad Dody; Melati, Dini Sari (LPPM STT Terpadu Nurul Fikri, 2024)
Technology has had a significant impact on various aspects of human life, one of which is education through the implementation of e-learning as a modern learning solution. Technology makes the teaching and learning process easier thereby improving the quality of teaching and learning. The presence of the COVID-19 pandemic has also accelerated the transition of education to e-learning, although not all countries are fully prepared to implement it. This is also the case in Batam City, which has implemented e-learning in a number of schools and universities with support from academics and the local Education Office. The presence of e-learning offers learning flexibility but also presents challenges, such as learner dissatisfaction that affects low learning motivation. Therefore, this study aims to analyze the factors affecting e-learning user satisfaction among students with the research target of students in Batam City. The research was conducted using quantitative method and processed using SPSS. The results stated that e-learning satisfaction is influenced by system quality, internet quality, information quality and service quality. Therefore, to optimize the satisfaction of e-learning users must pay attention to these four factors.